CLASS: A Framework for Strategic Thinking and Actions during Academic and Workplace Transitions - Adam Denney; Sarah C. Williams; Danielle Dietz; Alysha Gray (Journal of College Orientation, Transition, and Retention)
The CLASS framework is a versatile tool college students can use when learning how to proactively and intentionally navigate new educational and work environments. It provides a concrete strategy for strategic thought processes, routines, and dialogues that can be adapted to fit different student support models.